Perioperative Fluid Management for Pulmonary Resection Surgery and Esophagectomy. (March 2014) - Chau, Edmond Hung Leong; Slinger, Peter
Perioperative fluid management is of significant importance during pulmonary resection surgery and esophagectomy. Excessive fluid administration has been consistently shown as a risk factor for lung injury after thoracic procedures. Probable causes of this serious complication include fluid overload, lung lymphatics and pulmonary endothelial damage. Along with new insights regarding the Starling equation and the absence of a third space, current evidence supports a restrictive fluid regimen for patients undergoing pulmonary resection surgery and esophagectomy. Multiple minimally invasive hemodyamic monitoring devices, including pulse pressure/stroke volume variation, esophageal Doppler, and extravascular lung water measurement, were evaluated for optimizing perioperative fluid therapy. Further research regarding the prevention, diagnosis, and treatment of acute lung injury after pulmonary resection and esophagectomy is required.